Economics, organization, and management - Milgrom, Paul R. (Prentice-Hall, 1992)
A systematic treatment of the economics of the modern firm, this book draws on the insights of a variety of areas in modern economics and other disciplines, but presents a coherent, consistent, innovative treatment of the central problems in organizations of motivating people and coordinating their activities. Introduces the fundamental problems organizations encounter and explains why they occur. Discusses a number of patterns of response — showing why organizations are structured as they are, why they adopt the policies they do, and how they solve organizational problems themselves.